COLLABOTIVE GOVERNANCE DALAM PENANGGULANGAN STUNTING DI KECAMATAN KARAWACI KOTA TANGERANG - Mahdiar; Mulyadi, Edi; Hardian, Dafyar Eliadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze the implementation of Collaborative Governance in stunting reduction in Karawaci District, Tangerang City, using the Ansell & Gash theoretical framework. Stunting is understood as a multidimensional issue that cannot be addressed sectorally but requires collaboration across actors, including government, community, and non-governmental organizations. This study employed a qualitative approach, collecting data through in-depth interviews, observation, and documentation. The informants included local government officials, health workers, Posyandu (Integrated Service Post) cadres, the Family Welfare Movement (PKK), and community leaders. The results indicate that the initial conditions for stunting reduction in Karawaci were characterized by limited resources and differing interests, but were driven by the urgency of the problem and the political commitment of the city government. Facilitative leadership implemented by the sub-district head and relevant agencies was a driving factor in cross-sectoral coordination. Institutional design remained weak because formal forums were not yet fully institutionalized, so collaboration relied more on social networks. The collaborative process has built trust, intensive communication, and shared understanding, despite challenges such as inaccurate data. Intermediate outcomes are seen in increased public awareness and increased coverage of nutrition services, while long-term outcomes still face challenges in policy sustainability and consistent resource support. The conclusion of this study confirms that Collaborative Governance in stunting reduction in Karawaci District is already underway, but remains fragmented and requires stronger institutionalization to ensure program sustainability. This research provides a theoretical contribution, demonstrating that the success of collaboration is not solely determined by formal regulations but also influenced by facilitative leadership, trust between actors, and the success of achieving small wins as a driving force for long-term collaboration. Keywords: Collaborative Governance, Stunting, Prevention, Karawaci District.